English language learning motivation of sports exchange students - Fatona Suraya; Setya Rahayu; Mawarni Mohamed; Ani Mazlina Dewi Mohamed; Miranti Nur Anggrahini (CV Rezki Media, 2021)
One of the benefits from students exchange program is to learn a foreign language. In the Faculty of Sports Science, UNNES, most students going abroad all-around Southeast Asia which English is the medium of instruction between countries. Thus, the exchange program were likely helped to motivate them to learn English. However, limited studies have discussed the English learning motivation of students who have been studying abroad. This study aims to explain the students’ motivation to learn English after being exposed to the exchange experience. The study explains their motivation in two domains: intrinsic and extrinsic motivation. It is descriptive quantitative research with a set of questionnaires as the primary source of data supported by interviews as the secondary data. The subjects of this study are 37 students from 4 majors; sports science (12), public health (11), physical education (7), and coaching education (7) which consisted of 20 females and 17 males, under the Faculty of Sports Science, UNNES who experienced the exchange programs between 2018-2019. The study found that personal belief on the importance of English to upgrade self-capacity, followed by practical practice of independent study to upgrade English performance, are the intrinsic motivational factors embraced by the exchange students. Furthermore, the exchange students’ view of the importance of English for their future career and the positive opinion from their environment on the people who can speak English have extrinsically motivated them to learn English. Future study needs to involve bigger participants by comparing those exchange and non-exchange students and examine the role of motivation toward the student's learning performance.